2016
DOI: 10.1007/s11019-016-9723-4
|View full text |Cite
|
Sign up to set email alerts
|

Value-impregnated factual claims and slippery-slope arguments

Abstract: Slippery-slope arguments typically question a course of action by estimating that it will end in misery once the first unfortunate step is taken. Previous studies indicate that estimations of the long-term consequences of certain debated actions, such as legalizing physician-assisted suicide, may be strongly influenced by tacit personal values. In this paper, we suggest that to the extent that slippery-slope arguments rest on estimations of future events, they may be mere rationalizations of personal values. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…7 Previously conducted studies have shown that the more controversial an issue is the more it tends to bring out personal emotional reactions and that personal values are often hidden and tacitly influence the estimation of factual claims. [3][4][5]9,10 The latter claim is partly analogous with the philosophy of science's claim that observations are influenced or tacitly impregnated by theories. 4,5 In the present study, we aimed to elucidate the values at stake when discussing PAS.…”
Section: Introductionmentioning
confidence: 90%
“…7 Previously conducted studies have shown that the more controversial an issue is the more it tends to bring out personal emotional reactions and that personal values are often hidden and tacitly influence the estimation of factual claims. [3][4][5]9,10 The latter claim is partly analogous with the philosophy of science's claim that observations are influenced or tacitly impregnated by theories. 4,5 In the present study, we aimed to elucidate the values at stake when discussing PAS.…”
Section: Introductionmentioning
confidence: 90%
“…Previously conducted studies have, however, indicated that Swedish physicians actually hold values that are in conflict with official values. [9][10][11][12][13][14][15][16][17][18] By official values in health care, we mean the values expressed in health care law and regulations. However, personal values that are at odds with the official values are seldom openly declared by the physician.…”
Section: Introductionmentioning
confidence: 99%
“…The simple idea is that the physician's personal values remain tacit while affecting factual judgements, so that the practical conclusion about what to do as a health care professional is informed by these values. [9][10][11][12][13][14][15][16][17][18][19] Value impregnation of factual aspects is not a phenomenon unique to Sweden or Swedish health care. In a Swiss study, Hermann et al investigate physicians' decision-making process regarding assisted suicide, claiming that physicians' personal values enter 'through the back-door' as they colour the assessment of patients' decision-making capacity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations